Nurse's Experience Program In Implementing Intravenal Chemotherapy Treatment In Cancer Patients: A Phenomenology Study - Kristian, Eben Haezar; Andri, Florensius; Widoroni, Christianus Eko Purwanto (Journal Of Nursing Practice, 2021)
Background: Cancer or malignant tumor is uncontrolled growth of cells or tissue and spreads from abnormal cells, if the spread is uncontrolled it can cause death. Experience is a very dynamic, complex and subjective phenomenon. One of the treatments for cancer patients is chemotherapy.Purpose: The purpose of this study was to explore the experiences of nurses in implementing intravenous chemotherapy treatment programs in cancer patients.Methods: This study uses a qualitative design with a phenomenological approach model to understand one's life experience and existing perceptions. The sampling technique used snow ball sampling. In this study, researchers will perform a snow ball sampling technique of participants who are at the Dr. Soedarso General Hospital. A total of ten nurses who work in the chemotherapy room participated.Result: The perception of nurses in providing intravenous chemotherapy services as a form of carrying out their assigned duties and responsibilities apart from curiosity to carry out chemotherapy and their empathy for patients. Support from nurses in providing intravenous chemotherapy services is obtained from the family even though they are reminded to always be careful (protected), from the hospital, especially the improvement of infrastructure and related policies as well as support from colleagues and doctors. Obstacles for nurses in providing intravenous chemotherapy services arise from the capacity of nurses and specialists who are less trained, the inadequate reporting system between nurses during service changes including infrastructure such as PPE, room size and medicine.Conclusion: Recommendations This study is expected to be used as a reference for future researchers related to the topic of nurse experiences that are still related to chemotherapy clients in cancer